Implementación de un sistema de comunicación, a través de la línea eléctrica, para las oficinas del Área de la Energía, las Industrias y los Recursos Naturales no Renovables. - Ambuludí Ordoñez, Miguel Angel (2011)
The development of a communication system, through the power line involved several stages of research, experimentation and design. It was based on the operation of IP networks. In this way, it was tried to use in the design devices that allow to couple the signal of the network with the signal sent from the transmitter to the receiver to form a system of connection. In an initial stage an investigation of the existing devices in the market was realized. All communication systems based on this method are commercially sent by means of a carrier, in the case of our communication is based on the integrated circuit IC LM 555. In chapter I we make a count of where the idea of ​​communication by Power line (plc) means. In the second chapter it is proposed to detail the different stages of the transmitter and receiver circuit that are used in a communication system The third chapter is reserved for the results obtained, as well as the conclusions and recommendations that we can give with the results. Next, in chapter four, the design of the transmitter and receiver card (pcb) required for each process of the communication system is shown, as well as the construction of the circuits necessary for the system according to each stage involved in the Project: general power supply, pilot lights, as well as wiring.